Notatk i filmowe Federica Felliniego. Notatnik reżysera jako manifest poetyki twórcy - Birkholc, Robert (Załącznik Kulturoznawczy, 2022)
The article is devoted to a little-known film Fellini: A Director’s Notebook (1969), which is included by the author in the so-called film “notes” – essayistic, selfreferential films depicting the directors’ work on fictional movies. As the author argues, Notebook … can be viewed as a kind of manifesto of the poetics (and even “semiotics”) of the artist’s films, which expresses its attitude to issues such as relations: director-actor, author-work, and film-reality through an essayistic form. Fellini plays with his image (appearing personally on the screen) and fictionalizes the non-fictional genre, creating a kind of “fake-documentary”. The subject and the quasi-documentary form of the “notes” allow the director to demonstrate an individual approach to the relationship between the film and reality. As the author argues, Notebook… was for Fellini a kind of transitional film, developing new artistic ideas – from then on, Fellini’s fictional works will be more and more essayistic, artificial, heterogeneous, and fragmentary.